Acidentes de trabalho em trabalhadores da Atenção Primária à Saúde das Regiões Sul e Nordeste do Brasil - Borges, Carla Luciane dos Santos (2012)
Job accidents in Brazil and in the world are one of the causes of sickness, limitations, disabilities and even death among workers. In the health area, studies are more focused on accidents in hospitals, although the Primary Attention to Health (APS) has about 1 million workers who act in environments with great risks of accidents due to the presence of chemical, physical and biological agents, besides the working itself being based on movement repetition, making it possible to potentiate its occurrence. It was aimed to identify the prevalence of job accidents among APS workers in 240 Basic Health Units of the Traditional and PSF attention models, in 41 cities with more the 100,000 inhabitants in the South and Northeast regions of Brazil. A cross-sectional study that used data from the Base Line Study of the Expansion and Consolidation Project of Family Health Strategy (ELB-PROESFUFPEL), performed in 2005. The adjusted analysis was performed with Poisson regression. The total sample was made of 4,741 workers. The prevalence of job accidents in APS was 34.8%. Among the accidents it stands out: with drill cutting material (62.4%), fall (36.1%), stroke (13.8%), shock (8.6%) and traffic accidents (23.0). In the adjusted analysis, the variables age, income, smoking, minor psychiatric disorders, work regime, occupation, adequacy, satisfaction with home assistance and team work were associated with the outcome. Characterize and register the occurrence of lifelong job accidents among APS workers, identifying the different occupational categories, the most exposed and other associated factors, can contribute to new security measures and resizing of workers health politics.